NEUTRON THERAPY IN THE TREATMENT OF RADIORESISTANT MALIGNANT TUMORS - L. I. Musabaeva; E. L. Choinzonov; O. V. Gribova; Zh. A. Startseva; V. V. Velikaya; V. A. Lisin (Сибирский онкологический журнал, 2016)
The results of the combined modality treatment including neutron therapy for patients with resistant malignant tumors were presented. Efficacy of neutron therapy was assessed using disease-free and 5-year survival rates. Neutron therapy used alone or as a combination therapy was shown to be more effective than photon therapy. A comprehensive program for the prevention and treatment of acute radiation-induced damages was devised.